Chronic bilateral renal denervation reduces cardiac hypertrophic remodelling but not β‐adrenergic responsiveness in hypertensive type 1 diabetic rats. Issue 6 (1st June 2015) - Thaung, H. P. Aye; Yao, Yimin; Bussey, Carol T.; Hughes, Gillian; Jones, Peter P.; Bahn, Andrew; Sammut, Ivan A.; Lamberts, Regis R.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Can bilateral renal denervation, an effective antihypertensive treatment in clinical and experimental studies, improve cardiac β‐adrenoceptor responsiveness in a diabetic model with underlying hypertension? What is the main finding and its importance? Bilateral renal denervation did not affect β‐adrenergic responsiveness in the diabetic hypertensive rat heart, but denervation reduced the hypertension‐induced concentric hypertrophic remodelling. This suggests that the positive haemodynamic changes induced by renal denervation are most likely to reflect an attenuation of sympathetic effects on the systemic vasculature and/or the renal function rather than direct sympathetic modulation of the heart. Bilateral renal denervation (BRD) has been shown to normalise blood pressure in clinical and experimental studies of hypertension by reducing systemic sympathetic output. This study determined the effect of BRD on cardiac β‐adrenoceptor (AR) responsiveness in a diabetic model with underlying hypertension using the transgenic (mRen‐2)27 rats. Bilateral renal denervation or sham surgeries were conducted repeatedly at 3, 6 and 9 weeks in Ren‐2 rats with or without streptozotocin (STZ)‐induced diabetes (4 × n = 7); Sprague–Dawley rats (n = 6) served as control animals. Cardiac function was determined in isolated hearts at 18 weeks of age. Normalised left ventricular developed pressure and relaxation was recorded in response to incremental concentrations of the β‐AR agonist isoprenaline (from 10−10 to 10−7 m) or the β3‐AR agonist BRL37344 (from 10−13 to 10−6 m). Expression levels of β1‐AR were determined by Western blot. Both inotropic and lusitropic β‐AR responsiveness was reduced in the hypertensive diabetic hearts, but these responses were unaltered after BRD. Expression levels of β1‐AR were increased after BRD (Sham, 0.85 ± 0.11 versus 1.01 ± 0.05 a.u.; BRD, 1.45 ± 0.11 versus 1.46 ± 0.07 a.u.; Ren‐2 versus Ren‐2 STZ, P < 0.05 versus Sham). No effect of β3‐AR agonist stimulation with BRL37344 was observed. Interestingly, BRD increased left ventricular diastolic volume in both the Ren‐2 and the Ren‐2 STZ groups. Bilateral renal denervation did not restore the attenuated cardiac β‐AR responsiveness in the diabetic hypertensive rats, but it reduced the extent of hypertension‐induced concentric hypertrophic remodelling. Thus, the haemodynamic protection offered by renal denervation appears to reflect an attenuated sympathetic innervation of the systemic vasculature and/or kidney rather than a direct cardiac effect.